RESPONSE OF POTASSIUM COMPOUNDS ON POST-HARVEST LIFE OF BER CV. BANARASI KARAKA - SONKARIYA, VIMAL SONKARIYA; SINGH1 , S. P; NIRGUDE, VISHAL (The Bioscan, 2024)
An experiment was conducted during 2013-14 to study the effect of potassium compounds on post-harvest life of uniform and healthy fruits of ber cv. Banarasi Karaka at golden yellow stage of maturity. The fruits weretreated with two potassium compounds viz., KNO3 and K2 SO4 at concentration levelsof 1%, 1.5% and 2%. The observations were recorded at 4 days interval (0th day, 4th day, 8th day and 12th day) during storage at ambient conditions. The treatment KNO3 @ 2% was found significantly superior in reducing the weight loss (5.65%), decay loss (8.65%) and acidity (0.156%) as well as increased TSS (15.30%) and ascorbic acid (69.80 mg/100g) of fruitson 12th day of storage. Fruits treated with KNO3 (2%) can be stored economically for 8 days in ambient conditions. Results indicated that foliar fertilization with KNO3 (2.0%) was found superior in maintaining quality and shelf life of the ber fruits.